Application of The Unified Theory of Acceptance and Use of Technology Method to Analyze Customer Acceptance Level of Electronic Parking Payment Systems - Sudirjo, Frans; Candra Dewi, Luh Komang; Dharmawan, Donny; Budiarto, Balla Wahyu; Amrin (Jurnal Informasi dan Teknologi, 2023)
This research aims to find out which variables most influence user acceptance of electronic payment systems. Researchers used a quantitative approach in their research. The students who used motorcycles and electronic payment methods made up the study's population. sampling strategy that combines purposive sampling with the non-probability sampling technique. There were one hundred responders in the study's entire sample. Researchers used observation, interviews, surveys, and related literature to gather the information they needed for this investigation. The elements that were demonstrated to have an impact on users' acceptance of electronic payment systems were behavioral intention, use behavior, social influence, performance expectancy, effort expectancy, and facilitating conditions, according to the research findings. The variable that most influences user acceptance of electronic payment systems is facilitating conditions for use behavior, which shows that users repeatedly use electronic payment systems because the management has adequate facilities and infrastructure and is commonly used in other public parking lots, such as card readers for tapping in and exit parking, as well as staff who help if there are difficulties and sufficient knowledge in using them.